Mortality and health issues : review of current situation and study guidelines - United Nations. Economic and Social Commission for Asia and the Pacific; Meeting on Analysis of Trends and Patterns of Mortality in the ESCAP Region (1984 : Bangkok) (Bangkok : Economic and Social Commission for Asia and the Pacific, 1985)
36